Eficiência do processo recuperacional : uma busca pela segurança jurídica à atividade empresarial, sob a ótica da análise econômica do direito - Coelho, Bruno Felipe Monteiro (2024)
This research seeks to establish a link between three specific points of law, which are procedural efficiency, recovery law and economic analysis of law. To this end, it carries out an analysis of the fundamental guarantee of procedural efficiency and its importance for a procedural environment, considering the need for legal certainty for its implementation, mainly in the negotiating environment of the insolvency system. In turn, judicial recovery is presented in its nuances from the perspective of a collective negotiating environment, where creditors can decide, depending on the incentives, to continue or terminate business economic activity, generating impacts not only for the specific process, but also for the whole society. Finally, the research ends with the analysis of how the tools studied by the economic analysis of law can help law enforcers to generate greater efficiency and legal security in the business environment established in the judicial recovery process. This entire framework was used, through qualitative and bibliographical research, aiming to answer the question established in the problem, regarding the possibility of the economic analysis of law presenting tools that can guarantee greater efficiency in the judicial recovery process. Having established all the parameters, the work points out that there are mechanisms related to the economy that deserve attention from both the legislator and the judge, since if applied they can guarantee greater procedural efficiency, since they have the power to influence decision-making of the economic agents involved in the recovery procedure.